PERAN STRUKTUR ORGANISASI DAN SISTEM REMUNERASI DALAM MENINGKATKAN KINERJA - Tatiek Nurhayati; Ahmad Darwansyah (Jurnal Ekonomi dan Bisnis, 2013)
This study focused on examining the influence of organizational structure, systems remunerasi, on work motivation in order to improve the performance of employees at the tax office in Semarang Region. Respondents in this study were employees of the Directorate General of Taxation in Semarang with the number of sampling 120 people. The results of data analysis showed that all the hypotheses proposed in this study is acceptable. This means that there are positive and significant influence of organizational structure variables, remunerasi system, to work motivation and employee performance in order to increase the tax directorate general region of Semarang. Thus through the efforts of organizational structure, systems that supportthe organization remunerasi be better in accordance with the changes being made, so as to motivate the work in order to improve the performance of employees so as to provide maximum service to the public, especially taxpayers. Processing of data obtained on the influence of the organizational structure of work motivation is 0.32; the influence of the system remunerasi of work motivation is 0.42; influence the organizational structure of the performance of employees is 0.21; remunerasi system influence on the performance of employees is 0.23; and the influence of motivation on employee performance is 0.25.Keywords : organization structure, remuneration system, work motivation, and employee performance